2022
DOI: 10.3390/pharmaceutics14071357
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Prophylactic Efficacy of Liposome-Based Vaccine against the Drug-Resistant Acinetobacter baumannii in Mice

Abstract: In recent years, the emergence of multidrug-resistant Acientobacter baumannii has greatly threatened public health and depleted our currently available antibacterial armory. Due to limited therapeutic options, the development of an effective vaccine formulation becomes critical in order to fight this drug-resistant pathogen. The objective of the present study was to develop a safe vaccine formulation that can be effective against A. baumannii infection and its associated complications. Here, we prepared liposo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…To evaluate the inhibitory activity of the S1032 compound on bacterial biofilm formation, the crystal violet staining assay was performed in this research. All the conduction was finished strictly under the guidance with only a little modification (Khan et al 2022). In short, A. baumannii strain were seeded in 96 well plates and cultured in the incubator at the condition of 37℃ for 24 h. After the bacterial biofilm formation, 0.1% crystal violet (CV) (Sigma) solution was added into wells for staining at 37 °C for 10 min.…”
Section: Biofilm Formation Assaymentioning
confidence: 99%
“…To evaluate the inhibitory activity of the S1032 compound on bacterial biofilm formation, the crystal violet staining assay was performed in this research. All the conduction was finished strictly under the guidance with only a little modification (Khan et al 2022). In short, A. baumannii strain were seeded in 96 well plates and cultured in the incubator at the condition of 37℃ for 24 h. After the bacterial biofilm formation, 0.1% crystal violet (CV) (Sigma) solution was added into wells for staining at 37 °C for 10 min.…”
Section: Biofilm Formation Assaymentioning
confidence: 99%
“…It may be because antibiotic pretreatment can enhance the protein expression of A. baumannii and produce a stronger immune response (Shu et al, 2016 ). Recently, the first study showed the protection of liposomes-encapsulated whole cell antigens (Lip-WCAgs) in infection model, Liposomes owned strong immunoadjuvant potential, Lip-WCAgs induced the higher production of antibody titers, stimulate immunocyte proliferation, the antisera from immunized mice can inhibited the biofilm formation, and 80% mice survived from challenge (Khan et al, 2022 ). The latest research shows that in addition to formalin inactivation, the relatively innovative radiation inactivation method also shows 80–100% protection ability (Dollery et al, 2021 ).…”
Section: Vaccinementioning
confidence: 99%